Resolving Clinicians’ Queries Across a Grid’s Infrastructure - Estrella, F.; del Frate, C.; Hauer, T.; McClatchey, R.; Odeh, M.; Rogulin, D.; Amendolia, S. R.; Schottlander, D.; Solomonides, T.; Warren, R. (Methods of Information in Medicine, 2005)
Objectives: The past decade has witnessed order of magnitude increases in computing power, data storage capacity and network speed, giving birth to applications which may handle large data volumes of increased complexity, distributed over the internet.Methods: Medical image analysis is one of the areas for which this unique opportunity likely brings revolutionary advances both for the scientist’s research study and the clinician’s everyday work. Grids [1] computing promises to resolve many of the difficulties in facilitating medical image analysis to allow radiologists to collaborate without having to co-locate.Results: The EU-funded MammoGrid project [2] aims to investigate the feasibility of developing a Grid-enabled European database of mammograms and provide an information infrastructure which federates multiple mammogram databases. This will enable clinicians to develop new common, collaborative and co-operative approaches to the analysis of mammographic data.Conclusion: This paper focuses on one of the key requirements for large-scale distributed mammogram analysis: resolving queries across a grid-connected federation of images.
Keywords: Distributed database; queries; meta-data; mammography; medical image analysis; epidemiological studies